Endogenous opioids regulate moment-to-moment neuronal communication and excitability - Bryony L. Winters (Nature Portfolio, 2017)
The endogenous opioid system regulates fear and anxiety, but the underlying cellular mechanism is unclear. Winterset al. shows that in the intercalated cells (ITC) of the amygdala, endogenous opioids suppress glutamatergic inputs via the δ-opioid receptor presynaptically, and reduce the excitability of ITCs via the μ-opioid receptor postsynaptically.